2018
DOI: 10.1111/joms.12410
|View full text |Cite
|
Sign up to set email alerts
|

Struggling with Meaningfulness when Context Shifts: Volunteer Work in a German Refugee Shelter

Abstract: This article draws on an ethnographic study of volunteer work in a German refugee shelter to explore how individual experiences of meaningfulness are intertwined with shifting discursive and organisational contexts. At the beginning of the so‐called refugee crisis, societal discourses portrayed this volunteer work as extraordinarily meaningful – a state we capture through the metaphor of ‘overflow’. This ‘overflow’ mobilised volunteers and was an important point of reference for framing their work experiences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 106 publications
4
78
1
1
Order By: Relevance
“…Drawing on self-determination theory, our findings highlight the relevance of the societal legitimation of alternative career options (including less commonly chosen careers such as self-employment) to enable everyone to make truly volitional choices about their career. This complements existing explanations of how context affects meaningfulness at work, which emphasize congruence with societal values and norms ( Florian et al, 2019 ; Lepisto and Pratt, 2017 ) rather than enhancing the diversity of choice sets.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…Drawing on self-determination theory, our findings highlight the relevance of the societal legitimation of alternative career options (including less commonly chosen careers such as self-employment) to enable everyone to make truly volitional choices about their career. This complements existing explanations of how context affects meaningfulness at work, which emphasize congruence with societal values and norms ( Florian et al, 2019 ; Lepisto and Pratt, 2017 ) rather than enhancing the diversity of choice sets.…”
Section: Introductionsupporting
confidence: 64%
“…Moreover, we offer new insights on how meaningful work can be shaped by societal contexts that past reviews on meaningful work have called for ( Bailey et al, 2019 , p. 22). While there is first research that suggests that the changing legitimacy of social issues can impact the meaningfulness of volunteers' work ( Florian et al, 2019 ), we offer a complementary lens. This lens emphasizes how social legitimacy of more ‘niche’ career options, which are typically only picked up by a minority of individuals in the workforce, enables volitional choice even for those who do not embrace this career and thereby enhances their meaningfulness of work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CSR is seen as helping workers gain a greater sense of engagement with their work by infusing a greater sense of purpose in their activities (Aguinis and Glavas, 2019). On the other hand, some more critical sociological research regards meaningfulness as a potentially ‘overflowing’ if not ‘overloaded’ organizational element that could create dysfunctional effects (Florian et al, 2019). Integrating both perspectives could help explain why and how CSR professionals and other employees sometimes experience CSR-related forms of meaningfulness, and how these relate to organizational outcomes.…”
Section: Addressing Common Blind Spots and Leveraging Complementaritimentioning
confidence: 99%
“… 27 One study demonstrated the importance of exploring motivation through an anthropological lens, showing how changing socio-political contexts influenced volunteer engagement during Germany’s immigration crisis. 28 Volunteers initially borrowed from broader public discourses to attribute meaning to their efforts with refugees, but as the socio-political relations with refugees changed, they altered the ‘meaningfulness’ of their work by drawing on new social discourses about migrants. We appreciatively draw from this approach.…”
Section: Introductionmentioning
confidence: 99%